2008
DOI: 10.1063/1.3056635
|View full text |Cite
|
Sign up to set email alerts
|

Drift current dominated terahertz radiation from InN at low-density excitation

Abstract: This letter investigates the polarity of terahertz radiation from indium nitride (InN) excited by femtosecond optical pulses wherein a central wavelength of around 790nm is measured. The InN epilayers are grown by metalorganic chemical vapor deposition on sapphire and silicon substrates. The polarity of the terahertz radiation field from InN is opposite to that from p-InAs whose radiation mechanism is dominated by the photo-Dember effect indicating that the dominant radiation mechanism in InN is the drift curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…As a result, the terahertz wave polarities of n-type and p-type InN due to the surface electric field are both negative. Recently, Lin et al 15 reported the observation of the negative polarity of terahertz wave from an undoped n-type InN excited at very low fluence below 0.6 J / cm 2 , indicating that terahertz radiation is attributed to the drift current induced by the internal surface electric field. For highly excited InN, however, terahertz radiation induced by the surface electric field is overpowered by the photoDember field so that its polarity is positive.…”
mentioning
confidence: 98%
“…As a result, the terahertz wave polarities of n-type and p-type InN due to the surface electric field are both negative. Recently, Lin et al 15 reported the observation of the negative polarity of terahertz wave from an undoped n-type InN excited at very low fluence below 0.6 J / cm 2 , indicating that terahertz radiation is attributed to the drift current induced by the internal surface electric field. For highly excited InN, however, terahertz radiation induced by the surface electric field is overpowered by the photoDember field so that its polarity is positive.…”
mentioning
confidence: 98%
“…A vast array of compound semiconductors has been examined with regard to their material parameters, including InAs, InSb, GaAs, and InP [1]. The THz radiation emitted from these materials has been attributed to either transient dipole current generation caused by the potential gradient in depletion regions or the large diffusion velocity difference between electrons and holes (referred to as the photo-Dember effect) while the nonlinearity contribution is sometimes ignored in single crystalline materials, as in the case of semiconductors grown along the [100] axis (in the case of zinc-blende semiconductors [2]) or c-axis (in the case of wurzite semiconductors [3]) at low excitation fluence regime. In the case of GaAs, THz radiation has been found to originate from surge currents by the surface electric field [4,5], whereas the radiation from InAs is mainly governed either by the photoDember effect in a thick scale (similar to that of the diffusion length) [2,6] or by carrier drift motion in the smaller thickness region (similar to the thickness of the surface-space charge layer (SCL)) [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, this dominant contribution of drift current is not observed in the studies of Wilke et al 3) and Wang et al 5) In our previous study, the THz radiation mechanism in n-type InN is attributed to drift current induced by the surface accumulation field and the spontaneous polarization-induced electric field at low-density excitation. 6) THz radiation due to both the photo-Dember effect and internal electric-field acceleration depends closely on carrier concentration. 4,7) Up to now, most literature focuses on THz radiation intensity, but the exact mechanism of THz radiation in native n-type InN with different electron concentrations is still controversial.…”
mentioning
confidence: 99%